Adaptation of the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) into French-Canadian and English-Canadian. Issue 2 (2008) - Coffin, Donna; Duval, Karine; Martel, Simon; Granton, John; Lefebvre, Marie-Claude; Meads, David M; Twiss, James; McKenna, Stephen P
Abstract : BACKGROUND: The Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) is the first disease-specific instrument for assessing patient-reported symptoms, functioning and quality of life (QoL) in pulmonary arterial hypertension (PAH). OBJECTIVES: To create and validate French-Canadian (FC) and English-Canadian (EC) language versions of the CAMPHOR. METHODS: A translation panel (for the FC version) and lay panels (for both versions) were convened to adapt the questionnaires (dual-panel methodology). Subsequently, these new questionnaires were field-tested in 15 FC PAH and 15 EC PAH patients. Finally, in a postal validation study, the new language versions of the CAMPHOR underwent psychometric evaluation in 41 FC and 52 EC PAH patients to test for reliability and validity. RESULTS: The FC and EC field-test interview participants found the questionnaires relevant, comprehensible and easy to complete. Psychometric analyses showed that the FC and EC adaptations were successful. High test-retest coefficients for the scales after controlling for change in respondent's QoL (FC: 0.92 to 0.96; EC: 0.85 to 0.99) indicated a high degree of reliability. The FC and EC CAMPHOR scales had good internal consistency (Cronbach's alpha coefficients 0.90 to 0.92 and 0.88 to 0.92, respectively). Predicted correlations with the Nottingham Health Profile provided evidence of the construct validity of the FC and EC scales. The FC and EC adaptations also showed known groups validity. CONCLUSIONS: The FC and EC adaptations of the CAMPHOR have been shown to be reliable and valid for measures of health-related QoL and QoL in PAH, and thus can be recommended for use in clinical studies and routine practice in PAH.